Neo-sex Chromosomes in the Monarch Butterfly, Danaus plexippus - Mongue, Andrew J; Nguyen, Petr; Voleníková, Anna; Walters, James R (G3 (Bethesda, Md.), 2017)
We report the discovery of a neo-sex chromosome in the monarch butterfly, Danaus plexippus, and several of its close relatives. Z-linked scaffolds in the D. plexippus genome assembly were identified via sex-specific differences in Illumina sequencing coverage. Additionally, a majority of the D. plexippus genome assembly was assigned to chromosomes based on counts of one-to-one orthologs relative to the butterfly Melitaea cinxia (with replication using two other lepidopteran species), in which genome scaffolds have been mapped to linkage groups. Sequencing coverage-based assessments of Z linkage combined with homology-based chromosomal assignments provided strong evidence for a Z-autosome fusion in the Danaus lineage, involving the autosome homologous to chromosome 21 in M. cinxia Coverage analysis also identified three notable assembly errors resulting in chimeric Z-autosome scaffolds. Cytogenetic analysis further revealed a large W chromosome that is partially euchromatic, consistent with being a neo-W chromosome. The discovery of a neo-Z and the provisional assignment of chromosome linkage for >90% of D. plexippus genes lays the foundation for novel insights concerning sex chromosome evolution in this female-heterogametic model species for functional and evolutionary genomics.
Keywords: Genetic Linkage; Lepidoptera; genomics; Sex Chromosomes; Male; motýli; sex chromosomes; Animals; pohlavní chromozomy; Female; mužské pohlaví; ženské pohlaví; genetická vazba; Butterflies; evolution; chromosomal fusion; zvířata